Incarceration and Incapacitation: Evidence from the 2006 Italian Collective Pardon - Buonanno, Paolo; Raphael, Steven (American Economic Review, 2013)
In August 2006, the Italian government released one-third of the nation's prison inmates via a national collective pardon. We test for a discontinuous break in national crime rates corresponding to the mass release. We also test for the effect of the return of the incarceration rate to its predicted steady state level on national crime rates. Finally, we exploit regional variation in prison releases based on the province of residence of pardoned inmates. All three sources of variation yield substantial incapacitation effect estimates and suggest that the crime-preventing effects of incarceration diminish with increases in the incarceration rate. (JEL K42)